Exploring the link between dietary thiamine and type 2 diabetes mellitus risk in US adults aged 45 years and older: Insights from a cross-sectional investigation. - Hong Lin; Zhengwei Gao; Hengfan Ni; Jian Li; Haoran Liu; Bo Qin; Zhiyao He; Zhaohui Jin (PLoS ONE)
The correlation between dietary thiamine intake and the incidence of type 2 diabetes mellitus (T2DM) remains a subject of controversy within the academic community. While numerous studies have attempted to elucidate this relationship, conclusive evidence remains elusive. A survey of U.S. adults aged 45 years and older examined the supposed association between dietary thiamine intake and the risk of developing T2DM with the aim of clarifying the potential link. In this cross-sectional investigation, we evaluated dietary thiamine intake data sourced from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2020. Using weighted multivariate logistic regression analysis, we assessed the potential risk of T2DM associated with varying levels of thiamine intake. The observation of nonlinear relationships was accomplished by fitting smoothed curves. This study ultimately included 15,231 participants aged 45 years and older. Dietary thiamine intake (after log transformation) was inversely related to T2DM after accounting for potential confounders (OR = 0.86, 95% CI: 0.78, 0.95). An increase in dietary thiamine intake by one unit is associated with a 14% reduction in the risk of T2DM. Furthermore, our analysis revealed that the associations between dietary thiamine intake and T2DM risk, such as age, gender, race, smoking status, alcohol use, hypertension, body mass index (BMI), and cardiovascular disease (CVD), remained consistent across multiple stratified subgroups (p values >0.05). According to this study, dietary thiamine intake may be associated with the incidence of T2DM among US residents aged 45 years and older. Appropriate increases in dietary thiamine intake are expected to offer substantial preventive potential for T2DM and significant clinical implications.